Demystifying the impact of service climate and internal service quality on managerial outcomes: Interactive effects of role stressors and managerial levels - Redden, Fabian Angelo (Curtin University, 2024)
Past studies show that service climate and internal service quality positively influence managerial well-being and performance, however, they do not explain the socio-psychological mechanism underlying this phenomenon. This study addresses this gap with an integrative conceptual model and a set of testable hypotheses. Specifically, it argues that internal service quality would partially mediate the negative effect of service climate on role stressors and fully mediate its positive effect on managerial well-being.